D2.6 Promote co-creation and innovation - Loureiro, S. M. C. (2022)
To promote the use of innovative data analytics techniques within local tourism stakeholders (SMEs and municipalities), the WP2 aims to create various Web-based application modules of data analyses that empower entrepreneurs and municipalities to improve their performance by means of tracking their current indicators, fostering best practices, and exchanging processes and solutions. In the task of Promote co-creation and innovation a community of multiple partners (e.g., SMEs owners, Municipalities, Suppliers, Tourist) will be created with the objective to promote relationship, synergies, interactions, and cooperation to co-create innovative products and solutions and share best practices. The process of creation of this tool will start with a cluster of 15 SMEs from each municipality, suppliers of such SMEs, as well as tourists and municipalities will be called to participate. The forum is a way to schedule meetings, expose good practices, exchange tips, expose problems, and help create solutions. The objective of these months from the beginning of the project until October 2022 was the first selection of possible solutions, analyse and teste them, namely: Streamyard, YouTube channel, and Zoom platform. The stakeholders who will benefit from the use of innovative data analytics techniques are the SMEs, municipalities, suppliers and tourists. The functionality of the innovation data analytics techniques, through a community of multiple partners, is to empower SMEs, municipalities, and suppliers with techniques that allow them to exchange ideas, best practices and measures tools to improve the service that they offer and become more competitive.